Morphological aspects of the testes of 18 species of terrestrial of Heteroptera from Northwestern São Paulo (Brazil) - Gomes, Mariana Oliveira [UNESP]; Castanhole, Márcia Maria Urbanin [UNESP]; Souza, Hederson Vinicius De [UNESP]; Murakami, Aline Sumitani [UNESP]; Firmino, Tatiani Seni De Souza [UNESP]; Saran, Priscila Samara [UNESP]; Banho, Cecilia Artico [UNESP]; Monteiro, Leticia Da Silva [UNESP]; Silva, Jocielly Cristina Pereira Da [UNESP]; Itoyama, Mary Massumi [UNESP] (Instituto Virtual da Biodiversidade | BIOTA - FAPESP, 2013)
The Heteroptera are known for their odour, for being pests or for being disease carriers. However, they are still not extensively studied, perhaps because they form a very large group. Therefore, with the aim of enhancing the knowledge of the morphology of the testes of this insect order, we collected and analysed 18 species of terrestrial Heteroptera from the northwestern part of São Paulo. The analysis of these species revealed some differences between the testicles of these species, including their shape (elongated, oval, round or pecten), the morphology of the testicular lobes (elongated and paired side by side or united in a single region), the colours of the peritoneal sheath that surrounds the lobes (red, orange, yellow or translucent), and the number of testicular lobes (one, two, four, five, six or seven). Because the aspects analysed were highly variable, our study suggests a need for further analysis of Heteropteran testicular morphological differences.

Os Heteroptera são organismos conhecidos pelo seu odor, por serem pragas ou por serem transmissores de doenças, contudo, eles ainda são pouco estudados, talvez por formarem um grupo muito grande. Portanto, com o objetivo de ampliarmos as informações dos aspectos testiculares deste grupo analisamos 18 espécies de Heteroptera terrestres pertencentes a oito famílias que foram coletadas no Noroeste Paulista. Através das análises dessas espécies foi observado diferenças testiculares quanto: a sua forma (alongadas; ovalados; forma de concha, denominada pecten; ou arredondados); a morfologia dos lobos (alongados e pareados lado a lado ou unidos em uma única região, na forma de um “ofiuroide”); às cores da bainha peritoneal (alaranjada, amarelada, avermelhada ou transparente); ao número de lobos testiculares (um, dois, quatro, cinco, seis, sete). Devido aos aspectos analisados serem muito variáveis, nosso estudo sugere um aprofundamento maior na questão que envolve as diferenças morfológicas testiculares.
Aspectos testiculares de 18 espécies terrestres de Heteroptera do Noroeste de São Paulo (Brasil)
Keywords: testicles; peritoneal sheath; lobes; testículos; bainha peritoneal; lobos